Greater than the sum of your parts: Nonlethal stable isotope sampling methods in spiders. Issue 1 (27th January 2022) - Marker, Jeffery; Lafage, Denis; Bergman, Eva; Bowes, Rachel E.
Abstract: As top consumers and generalist predators, spiders are ideal organisms to study food webs and complex ecological functions using stable isotopes. Most researchers use whole‐body samples to analyze stable isotope ratios in spiders. Spiders can regrow lost legs and produce multiple molts during a life cycle, and nonlethal sampling utilizing legs and molts may provide a useful alternative to whole‐body sampling especially in larger bodied or threatened species. Furthermore, removing spider abdomens and thus leftover prey in the gut contents may provide a more accurate isotopic value. We tested the hypothesis that the δ 15 N, δ 13 C, or δ 2 H isotopic values in spider legs are reliable proxies for spider prosomas, abdomens, or whole bodies. We used laboratory‐reared large‐bodied spiders ( Pterinochilus murinus ) and field‐collected Lycosidae to compare lethal and nonlethal tissue isotopic values. We found that nonlethal samples of spider legs and molts are acceptable alternatives to lethal whole‐body samples to determine δ 13 C and δ 15 N stable isotope signatures. Nonlethal samples are not suitable proxies for whole‐body samples to determine δ 2 H isotopic values. Using nonlethal leg or molts samples in stable isotope investigations of spiders will allow researchers to promote conservation efforts and study threatened species while ensuring accurate and repeatable results.